The Effect of Policy on Business Competitiveness of Bali Cattle Farming in Kupang District, East Nusa Tenggara, Indonesia - Melkisedik Bukifan; Harianto; Bayu Krisnamurthi (Jurnal Manajemen & Agribisnis, 2021)
Bali cattle are Indonesian indigenous cattle and bred by most households in East Nusa Tenggara (NTT) province. East Nusa Tenggara is one of the main production centers of beef cattle. However, the growth production rate of Bali cattle in NTT tends to decline, while Indonesian import rates of cow and meat are still increasing. This research aims to analyze the competitiveness level of Bali cattle. Policy Analysis Matrix was employed to determine the level of profit and competitiveness of cattle breeding at the household level, according to local agriculture officials, 140 breeders from 2 sub-district areas of Kupang were chosen as respondents. The results show that the cattle fattening farms have shown positive private and social profits and high level of competitiveness. Therefore, the appropriate government’s policies toward the inputs and outputs are needed to increase the efficiency of Bali cattle production at household level. Keywords: Bali cattle breeders, competitiveness, policy analysis matrix